2011
DOI: 10.1038/srep00180
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of LMP2 as tumor-suppressor defines new targets for uterine leiomyosarcoma therapy

Abstract: Although the majority of smooth muscle neoplasms found in the uterus are benign, uterine leiomyosarcoma (LMS) is extremely malignant, with high rates of recurrence and metastasis. We earlier reported that mice with a homozygous deficiency for LMP2, an interferon (IFN)-γ-inducible factor, spontaneously develop uterine LMS. The IFN-γ pathway is important for control of tumor growth and invasion and has been implicated in several cancers. In this study, experiments with hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
105
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(121 citation statements)
references
References 54 publications
(90 reference statements)
7
105
0
Order By: Relevance
“…A pathological examination of surgical samples revealed the presence of a mass measuring 3 cm in its largest diameter in the lumbar quadrate muscle without a fibrous capsule. All lymph nodes were negative for human Ut-LMS metastases, and immunohistological studies showed positivity for ki-67 and negativity for LMP2/β1i [37]. Histological findings were consistent with metastatic Ut-LMS for the skeletal muscle and rectum lesions [37].…”
Section: Biological Role Of Lmp2/β β β β1i In Uterine Mesenchymal Tumsupporting
confidence: 48%
See 3 more Smart Citations
“…A pathological examination of surgical samples revealed the presence of a mass measuring 3 cm in its largest diameter in the lumbar quadrate muscle without a fibrous capsule. All lymph nodes were negative for human Ut-LMS metastases, and immunohistological studies showed positivity for ki-67 and negativity for LMP2/β1i [37]. Histological findings were consistent with metastatic Ut-LMS for the skeletal muscle and rectum lesions [37].…”
Section: Biological Role Of Lmp2/β β β β1i In Uterine Mesenchymal Tumsupporting
confidence: 48%
“…2) (NOTE 1) . Of the 54 cases we examined with human Ut-LMS, 46 were negative for LMP2/β1i expression, 4 were focally positive, and 2 were partially positive [37]. Two Ut-LMS cases stained for LMP2/β1i.…”
Section: Biological Role Of Lmp2/β β β β1i In Uterine Mesenchymal Tummentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, costimulatory molecules such as CD80 or CD86 are often absent from the surface of tumour cells, which makes activation of T lymphocytes impossible (37,46). Other molecules whose expression may be downregulated in tumour cells are latent membrane protein 2 (LMP2), latent membrane protein 7 (LMP7), transporter associated with antigen processing protein (TAP protein), and tapasin (17,23,32). Most tumour antigens that have been identified are proteins which are also found on other cells in the body, leading to the phenomenon of immune tolerance to tumour antigens (24).…”
mentioning
confidence: 99%